Design and cost estimation of solar powered reverse osmosis desalination system. (June 2021) - Saleem, Muhammad Wajid; Abbas, Asad; Asim, Muhammad; Uddin, Ghulam Moeen; Chaudhary, Tariq Nawaz; Ullah, Asad
Photovoltaic assisted reverse osmosis (PV-RO) has been proven an efficient renewable energy-based desalination technique to provide drinkable water, especially in remote areas. In this manuscript, a simulation based RO design system was adopted to evaluate the desalination performance for three cities of Pakistan, that is, Lahore, Hasil Pur, and Faisalabad. The inlet concentration of Lahore, Hasil Pur, and Faisalabad was reduced from 1495, 2190, and 7683 TDS to 295.44, 237.69, and 241.98 TDS respectively, according to the WHO drinking water recommendations. The RO desalination system was integrated with the photovoltaic system to fulfill the energy requirement for desalination. The energy requirement for the RO system for the working of 10 h/day with the freshwater production rate of 0.80 m 3 /h for Lahore, Hasil Pur, and Faisalabad is 60, 95, and 311 kWh/month, respectively. According to PVsyst software, the energy demand can be accomplished by installing 9 PV panels in Lahore, 15 PV panels in Hasil Pur, and 40 PV panels in Faisalabad. The simulation results in PVsyst showing that the battery losses will be 52.2% in Lahore, 51.1% in Hasil Pur, and 49% in Faisalabad.